Characteristics of the Density and Magnetic Susceptibility of Pumice from the Maninjau Caldera-Forming Eruption, Indonesia - Hidayatul Lisma, Rahmi; Rifai, Hamdi; Forni, Francesca; Syafriani; Ratnawulan; Gustika Yonanda; Mutiara Kusuma Febriwanti; Nur Azizah; Retna Junia; Anisa Janna; Amelia Roza Haqu (Jurnal Geologi dan Sumberdaya Mineral, 2024)
Abtract- Lake Maninjau is a volcanic caldera formed by a volcanic eruption located in West Sumatra. This volcanic eruption threw pyroclastic materials, one of which is pumice, as far as ± 75 km from the center of the eruption. This study aims to determine density and magnetic susceptibility characteristics of pumice from maninjau caldera-forming eruptions, indonesia. The method used is the rock-magnetic method. It is used to measure magnetic susceptibility based on the distribution of volcanic material. The samples were selected from 3 different locations around Mount Maninjau with distances varying between ±12-32 km. A Bartington Magnetic Susceptibility Metre Type B (MS2B) instrument was utilised to determine the susceptibility of rocks and X-ray fluorescence (XRF) to identify rock element levels. The results of the data analysis obtained have magnetic density and susceptibility values in the NGS (Ngarai Sianok) area, which ranged from 0.67-1.77×103 kg/m3 and 4.4-826×10-8m3/kg, the LBS (Lubuk Basung) area which ranged of 0.74-1.34×103 kg/m3 and 6.6-625.4×10-8m3/kg, and the PRM (Pariaman) area, which ranged from 0.68-3.63×103 kg/m3 and 8-359×10-8m3/kg. The results showed that when sampling closer to Mount Maninjau, the pumice is characterized by dense, fresh, but very small pore size and dominated by slightly greyish white pumice with few white crystals on its surface. Therefore, the location of the pumice from Mount Maninjau has a significant influence on its characteristics, including density, magnetic susceptibility, and iron (Fe) and titanium (Ti) content. Keywords: Pumice, Density, Magnetic Susceptibility, Mount Maninjau, XRF